العلاقة بين توقعات المعلم وردود الفعل والمثابرة على اداء المهام لدى ا طفال الابتدائي أثناء التربية البدنية - بودالي, أمين (Institut d’Éducation Physique et Sportive mostaganem 2020/2021, 2020)
ﺍﻟﻣﻠﺧﺹ: ﻋﻧﻭﺍﻥ ﺍﻟﻣﺫﻛﺭﺓ :ﺍﻟﻌﻼﻗﺔ ﺑﻳﻥ ﺗﻭﻗﻌﺎﺕ ﺍﻟﻣﻌﻠﻡ ﻭ ﺭﺩﻭﺩ ﺍﻟﻔﻌﻝ ﻭﺍﻟﻣﺛﺎﺑﺭﺓ ﻋﻠﻰ ﺃﺩﺍء ﺍﻟﻣﻬﺎﻡ ﻟﺩﻯ ﺃﻁﻔﺎﻝ ﺍﻻﺑﺗﺩﺍﺋﻲ ﺃﺛﻧﺎء ﺍﻟﺗﺭﺑﻳﺔ ﺍﻟﺑﺩﻧﻳﺔ. ﻟﻘﺩ ﺑﻳﻥ ﺍﻟﺑﺣﺙ ﺍﻟﻬﻡ ﻭ ﺍﻟﺗﻔﺭﻳﻁ ﻭﺍﻻ ﻣﺑﺎﻻﺓ ﺗﺟﺎﻩ ﻫﺫﻩ ﺍﻟﻣﺎﺩﺓ ﻭﻓﻲ ﺍﻟﻣﺭﺣﻠﺔ ﺍﻻﺑﺗﺩﺍﺋﻳﺔ ﺑﺎﻟﺧﺻﻭﺹ ﻭ ﺍﻟﺫﻱ ﻛﺎﻥ ﻧﺗﻳﺟﺔ ﺣﺗﻣﻳﺔ ﺍﻻﺳﺑﺎﺏ ﻭﻅﺭﻭﻑ ﻣﻭﺿﻭﻋﻳﺔ ﻧﺎﺗﺟﺔ ﻋﻥ ﺍﻷﺯﻣﺔ ﺍﻻﻗﺗﺻﺎﺩﻳﺔ ٬ ﻓﺎﻥ ﺍﻻﺯﻣﺔ ﺍﻻﻗﺗﺻﺎﺩﻳﺔ ﺃﺟﻳﺭ ﺍﻟﻭﺳﻁ ﺍﻟﺗﺭﺑﻭﻱ ﻋﻠﻰ ﺍﻟﻌﺯﻭﻑ ﻋﻥ ﺍﻟﻣﺎﺩﺓ ﺍﻧﻪ ﻟﻡ ﻳﻌﺗﻧﻲ ﺑﻬﺎ ﻭﻟﻡ ﺗﻭﻓﺭ ﻟﻬﺎ ﺍﻟﻭﺳﺎﺋﻝ ﻭ ﺍﻟﺗﺟﻬﻳﺯﺍﺕ ﻭ ﺍﻟﻣﻳﺎﺩﻳﻥ ﺍﻻﻟﺋﻘﺔ ﻭﺍﻟﻣﺎﻟﺋﻣﺔ ﻟﻣﻣﺎﺭﺳﺗﻬﺎ ﻭﺗﺄﺩﻳﺗﻬﺎ ﻓﻲ ﺍﻟﻣﺩﺍﺭﺱ . ﻗﺩ ﻳﻌﻭﺩ ﺫﻟﻙ ﺃﻳﺿﺎ ﺍﻻﺳﺑﺎﺏ ﻋﺩﻡ ﺗﻭﻓﻳﺭ ﺍﻟﻭﺳﻁ ﺍﻟﻡ ﺍﻟﺋﻡ ﻟﺗﻁﻭﻳﺭﻫﺎ ﻛﺗﻭﻓﻳﺭ ﺍﻟﻣﻧﺷﺎﺓ ﻭ ﺍﻟﺗﺟﻬﻳﺯ ﻭ ﺍﻟﺗﻣﻭﻳﻝ ٬ ﺑﺎﻟﺿﺎﻓﺔ ﺍﻟﻰ ﺍﻧﻌﺩﺍﻡ ﺍﻟﺗﺄﻁﻳﺭ ﻭﻋﺩﻡ ﻭﺟﻭﺩ ﻣﺧﺗﺹ ﻣﺅﻫﻝ ﻟﺗﻁﺑﻳﻘﻬﺎ ﻓﻲ ﺍﻟﻭﺳﻁ ﺍﻻﺑﺗﺩﺍﺋﻲ ٬ ﻛﻣﺎ ﻧﺷﻳﺭ ﺍﻟﻰ ﺇﻥ ﺍﻟﻅﺭﻭﻑ ﺍﻻﺟﺗﻣﺎﻋﻳﺔﻭ ﺍﻟﺯﻣﺔ ﺍﻻﻗﺗﺻﺎﺩ ﺓﻱ ﺍﻟﺗﻲ ﻣﺭﺕ ﺑﻬﺎ ﺍﻟﺟﺯﺍﺋﺭ ﻛﺎﻧﺕ ﻣﻥ ﺍﻻﺳﺑﺎﺏ ﺍﻟﻣﻭﺿﻭﻋﻳﺔ ﺍﻟﺟﻭﻫﺭﻳﺔ ﻓﻲ ﺇﻫﻡ ﺍﻟﻣﻣﺎﺭﺳﺔ ﻓﻲ ﺍﻟﻭﺳﻁ ﺍﻟﺗﺭﺑﻭﻱ ﻭ ﺑﺎﻟﺧﺻﻭ ﺹ ﻓﻲ ﺍﻟﻭﺳﻁ ﺍﻻﺑﺗﺩﺍﺋﻲ ٬ ﺑﺣﻳﺙ ﺭﻛﺯﺕ ﺍﻟﺩﻭﻟﺔ ﺍﻧﺷﻐﺎﻟﺗﻬﺎ ﻟﺣﻝ ﻣﺷﺎﻛﻝ ﺍﻟﻣﻭﺍﻁﻧﻳﻥ ﻋﻠﻰ ﻣﺳﺗﻭﻳﺎﺕ ﺍﺧﺭﻯ ٬ ﻓﺣﺎﻟﺔ ﺩﻭﻥ ﺗﻁﻭﻳﺭ ﺍﻟﻣﻣﺎﺭﺳﺔ ﻭﻫﺫﺍ ﻣﺎ ﺟﻌﻝ ﻣﺎﺩﺓ ﺍﻟﺗﺭﺑﻳﺔ ﺍﻟﺑﺩﻧﻳﺔ ﻓﻲ ﻁﻲ ﺍﻟﻧﺳﻳﺎﻥ ﻭ ﺍﻟﻧﺗﺎﺋﺞ ﻫﻭ ﺇﻫﻣﺎﻻﻟﺗﻛﻭﻳﻥ ﻭﻧﻘﺹ ﺍﻟﺗﺄﻁﻳﺭ ﻭﻋﺩﻡ ﺑﻧﺎء ﺍﻟﻣﻧﺷﺎﺓ ﺑﺎﻟﻣﺅﺳﺳﺎﺕ ﺍﻟﺗﺭﺑﻭﻳﺔ ٬ ﻭﻓﻲ ﺩﺭﺍﺳﺗﻧﺎ ﺍﻟﻣﻳﺩﺍﻧﻳﺔ ﻻﺣﻅﻧﺎ ﺑﻌﺩ ﺗﺣﻠﻳﻠﻧﺎ ﻟﻧﺗﺎﺋﺞ ﺍﺳﺗﺑﻳﺎﻥ ﺍﻧﻪ ﻫﻧﺎﻙ ﺗﻭﺟﻪ ﺗﺎﻡ ﻟﻭﺍﻗﻊ ﻣﺭﻳﺭ ﻟﺗﺭﺑﻳﺔ ﺍﻟﺑﺩﻧﻳﺔ ﻭ ﺍﻟﺭﻳﺎﺿﻳﺔ ﻓﻲ ﺍﻟﻁﻭﺭ ﺍﻻﺑﺗﺩﺍﺋﻲ ﺑﻝ ﺍﻧﺗﻘﻠﺕ ﻣﻥ ﻣﺎﺩﺓ ﺑﻳﺩﺍﻏﻭﺟﻳﺔ ﺑﺫﺍﺗﻬﺎ ﺍﻟﻰ ﻣﺟﺭﺩ ﻧﺷﺎﻁ ﺑﺩﻧﻲ ﺭﻳﺎﺿﻲ ﺗﺭﻓﻳﻬﻲ ﻳﻘﻭﻡ ﺑﻪ ﺃﺳﺗﺎﺫ ﻟﻳﺱ ﻟﻪ ﺃﻱ ﻣﻬﻧﺔ ﺃﻭ ﺍﺧﺗﺻﺎﺹ ﻣﻧﻬﺟﻲ ﻟﻣﻣﺎﺭﺳﺔ ﺍﻟﺗﺭﺑﻳﺔ ﺍﻟﺑﺩﻧﻳﺔ ﺍﻟﺭﻳﺎﺿﻳﺔ ﺍﻟﻣﻼﺋﻣﺔ ﻟﻠﻣﺭﺣﻠﺔ ﺍﻟﻌﻣﺭﻳﺔ ﺍﻻﻋﺗﺑﺎﺭ ﺍﻧﻪ ﺍﻟﻣﺟﺎﻝ ﻟﺗﺣﻘﻳﻕ ﺍﻟﻧﻣﻭ ﺳﻭﻯ ﺑﺎﻟﻌﻠﻡ ﺃﻱ ﺗﺭﻙ ﺍﻟﻣﺟﺎﻝ ﺍﻻﺧﺗﺻﺎﺹ . Summary: The title of the note: The relationship between teacher expectations, reactions and perseverance in performing tasks among children primary school during physical education. The research showed concern, negligence, and indifference towards this subject and in the primary stage in particular, which was the result of the inevitable causes and objective conditions resulting from the economic crisis. The economic crisis forced the educational community to abandon the subject because it did not take care of it and did not provide it with the means, equipment and fields Appropriate and appropriate practice and performance in schools. This may also be due to the reasons for not providing the appropriate environment for its development, such as providing the facility, equipment and financing, in addition to the lack of supervision and the absence of a qualified specialist to apply it in the primary environment. We also point out that the social conditions and the economic crisis experienced by Algeria were among the objective and fundamental reasons in the most important The practice in the educational environment, especially in the primary environment, so that the state focused its preoccupation with solving the problems of citizens at other levels, so there was no development of practice, and this is what made the subject of physical education in limbo, and the results are neglect of training, lack of framing, and failure to build the facility in educational institutions, and in Our field study, after analyzing the results of a questionnaire, noted that there is a complete orientation to the bitter reality of physical education and sports in the primary stage, but rather moved from a pedagogical subject in itself to a mere recreational sports physical activity carried out by a professor who does not have any profession or methodological specialization to practice physical education appropriate for the age stage. The consideration is that it is the field to achieve growth except with knowledge, i.e. leaving the field of competence.
LEPS-2021-7
Keywords: ﺍﻟﻁﻭﺭ ﺍﻹﺑﺗﺩﺍﺋﻲ - ﺍﻟﺗﺭﺑﻳﺔ ﺍﻟﺑﺩﻧﻳﺔ ﺍﻟﺭﻳﺎﺿﻳﺔ - ﺍﻟﺣﺭﻛﺔ ﺍﻟﺭﻳﺎﺿﻳﺔ ﺍﻟﻭﻁﻧﻳﺔ - ﺩﺭﺍﺳﺔ ﺇﺳﺗﻁﻼﻋﻳﺔ. / the primary phase - physical education - the national sports movement - an exploratory study